PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN ONLINE PAKAIAN DIKALANGAN MAHASISWA IKIP MUHAMMADIYAH MAUMERE - Nurliana (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
"The Influence of Prices on Online Purchase Decisions for Clothing Among Students of IKIP Muhammadiyah Maumere". Essay. Maumere: Faculty of Social Sciences and Humanities Education. IKIP Muhammadiyah Maumere, 2022. E-commerce is basically a trade transaction contact between sellers and buyers using internet media so that the process of ordering goods, payment transactions to delivery of goods is communicated via the internet. The development of Internet technology makes it easier for people to shop. Consumers/students no longer need to go to shopping centers or shops to shop. However, it is enough to use a gadget, consumers/students can shop by visiting various websites which are often referred to as online shopping. In improving consumer purchasing decisions, especially students of IKIP Muhammadiyah Maumere, producers should produce products and provide prices that can meet the needs, desires and attract the attention of consumers. The purpose of this study is to find out whether price has an effect on online purchasing decisions for clothing among students of IKIP Muhammadiyah Maumere. This research was conducted at the IKIP Muhammadiyah Maumere campus. The population of this study amounted to 275 students. The research sample was 73 students. The data analysis technique used simple linear regression analysis. Testing the data using the validity test, reliability test, normality test and the coefficient of determination test using the SPSS version 23 program. The results showed that price discounts had a positive effect on purchasing decisions by 13.2% and the remaining 86.8% was influenced by other factors that were not studied. in this research.